Investigating the Function of Check Dams on Sediment Control (Case Study: Watersheds of Eghlid, Marvdasht & Mamasani Regions of Fars Province) - S.S. D; M. S; N. T.B (مهندسی منابع آب, 2013)
Check dams are one of the most common alternatives for reducing watershed's sediment production, controlling erosion, stabilizing stream long profile and recharging water tables. In the Fars province, 70% of recent watershed measures for erosion and flood control consist of check dams. Considering that the function of check dams is related to environmental condition, therefore it may not be vise to judge about their function only on the basis of limited observations. So, this research has been carried out to determine the technical function of check dams in Fars province. In this research, 1056 check dams were investigated in Tavileh-Band watershed located in Eqlid, Tange-Shoul watershed located in Marvdasht and Jonagan watershed located in Mamasani of Fars province, and the capacity of check dams sedimentation and the volume of deposited sediments by existing check dams was determined by measuring and empirical methods. Meanwhile, sediment calculation was carried out by MPSIAC method. The results of the analyses and comparison of the amount of settled sediment with the amount of total generated sediment in each watershed indicated that, within 10 years, considerable amount of sediment were trapped behind the check dams at Eghlid and Marvdasht region. But because the check dams were damaged, part or all of the trapped sediment gradually escaped. Not repairing the damaged check dams allows the sediment to gradually tranport out of the watershed. Apart from the partial destruction of check dams, due to neglecting technical points in the construction of check dams such as choosing improper abutments of check dams or optimum parameters like the distance between the check dams in each channel system, the whole sedimentation capacity of check dams is not applied. At Mamasani region due to the perfect construction of the check dams and their stability, it's hopefully expected that in the following years much more sediment will be controlled, provided that the check dams are preserved well. According to the analyses, if all the steps of a watershed project including study, execution and maintenance management were carried out properly, it can be concluded that check dams will be completely efficient in all aspects of erosion and sediment management.